EVALUATION OF GOVERNMENT POLICY IN RELOCATING STREET VENDORS ALONG THE AXIS ROAD IN GOWA REGENCY - Kurnia Sari Tagari; Andi Cudai Nur; Muh Nur Yamin; Anisa Fitri (Jurnal Aktor, 2026)
This research aims to evaluate the Gowa Regency government's policy in relocating street vendors along the axis road. By using descriptive qualitative research methods and referring to James Anderson's second type of policy evaluation theory, this research analyzes the success rate of the relocation program through various aspects that have been determined by data collection techniques, namely, observation, interviews and documentation. The checking of data validity is done through source triangulation and technical triangulation. Data analysis techniques used data condensation, data presentation, and conclusion drawing. The results showed that the relocation policy of street vendors had varying degrees of success in the aspects evaluated. Three aspects showed positive results, namely improving environmental cleanliness, creating comfort for road users and the surrounding community, and improving the beauty of urban planning. However, there are two aspects that have not achieved optimal results, namely the aspect of order and the impact of relocation on traders. The order aspect still faces challenges in terms of traders' compliance with the established rules, while the impact of relocation raises various socio-economic consequences that need further attention from the local government.